Secondary syphilis presenting with jaundice. Issue 596 (June 1975) - Bhowmick, B. K.; Simpson, B.; Way, S. P. B.
Abstract : A patient with secondary syphilis presenting with jaundice is reported. Hepatic histology showed evidence of non-specific granuloma and active hepatitis but no cholestasis. This has been treated successfully with antisyphilitic therapy. The possibility of syphilitic pancreatitis and diabetes mellitus is discussed. The importance of serological tests for syphilis in jaundice of obscure origin is emphasized.